Pengaruh Harga dan Affiliate Marketing TikTok terhadap Keputusan Pembelian pada Generasi Z - Ramadhani, Dilla; Fadillah, Tri Dessy (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
The rise of social commerce via TikTok has transformed consumer behavior, particularly among Generation Z, who are known as digital natives. This study aims to analyze the influence of price and affiliate marketing on Generation Z’s purchasing decisions on TikTok. A quantitative method was employed, utilizing a survey design involving 200 Generation Z respondents who actively use TikTok and have made purchases through TikTok Shop. Data were analyzed using multiple linear regression. The results indicate that price has a positive and significant effect on purchasing decisions (t=8.569; p<0.001), as does affiliate marketing (t=6.257; p<0.001). Simultaneously, both variables together have a significant effect (F=157.630; p<0.001) with a contribution of 61.5%. The implications of this study provide guidance for businesses in designing effective pricing strategies and affiliate programs to reach Generation Z on the TikTok platform.